Medicinal Plants of the Genus Dioscorea L. Used in Traditional Thai Medicine Prescriptions - มณีนูน, เกศริน (KKU Science Journal, 2013)
The genus Dioscorea L. is distributed throughout the world and widely used in terms of food and medicinal plants. In Thailand, 42 species of Dioscorea L. have been revised. Revision results mention that this genus plays an important role as dietary plants. However, little study of the genus has been done in terms of medicinal uses. Three species of the genus, Dioscorea bulbifera L., D. hispida Dennst. and D. membranacea Pierre ex Prain and Burkill, are used in traditional medicine. Only one species, D. membranacea, has been reported. This review focuses on the uses of the genus Dioscorea which was reported in traditional medicine including related researches and further studies.